Oniomania: A Phenomenological Study on Online Shopping Addiction - de Guzman, Aiko; Acerit, Angelica; Baui, Nimfa Joy; Daliri, Jovilyn; Lazatin, Sonia Claire; Porto, Pio; Rabago, Zyrieshane; Rodriguez, Grashella; Valdez, Hazel Mae (International Journal of Arts, Sciences and Education, 2022)
This study aimed to determine the factors that drives participants to use online shopping applications and the impacts of online shopping addiction on participant's health and well-being, financial status, and relation to others. Semi structured open-ended questions were conducted used to gather data from the 15 participants. Based on the data collected, this study generated two sets of themes. Four themes in factors that drives participants to use online shopping applications/websites: (1) convenience; (2) boredom; (3) entertainment; (4) trendiness. Three themes in the impacts of online shopping addiction: (1) coping mechanism with stress and motivation to study (2) financial trouble and strained relationship and (3) impulsive and compulsive buying. Through a thorough analysis, it was found out that online shopping helps the participants to make shopping convenient, deal with boredom, spend leisure time (entertainment), and go with the trend induced by pandemic. While online shopping addiction serves as coping mechanism with stress and motivation to study. However, the results revealed that online shopping leads financial trouble, strained relationship and leads to impulsive and conclusive buying behavior. Keywords: Online shopping, Oniomania, Impulsive buying, Compulsive buying